Impact of heat stress on transcriptional abundance of HSP70 in cardiac cells of goat. Issue 3 (3rd May 2020) - Parida, S.; Mishra, S. R.; Mishra, C.; Mohapatra, S.; Dalai, N.; Mahapatra, A. P. K.; Kundu, A. K.
Abstract: The present study was aimed to document the effect of heat stress on the transcriptional abundance of heat shock protein 70 (HSP70) mRNA in cultured cardiac cells of goat. The heart tissues ( n  = 6) from different goats were used for the culture study. The cardiac cells obtained from different heart tissues were cultured in 24 well cell culture plates and incubated in a humidified CO2 (5%) incubator at 37 °C. The cardiac cells were allowed to become 75–80% confluent after 72 h of incubation. Thereafter, the cardiac cells were subjected to heat exposure at 42 °C (heat exposed) for 0, 20, 60 and 100 min. The cardiac cells exposed to heat stress at 42 °C for 0 min was taken as control. The relative abundance of HSP70 mRNA was gradually up-regulated ( p  < .05) from 20 to 100 min of heat exposure and reached the zenith ( p  < .05) at 100 min of heat challenge. The present finding highlights that, HSP70 could possibly act as a cytoprotective factor and may promote cardiac cell survival against the detrimental effect of heat stress. Moreover, this study may serve as the harbinger to conduct further research work on expression kinetics of HSP70 in cardiac cells of goat including other livestock species.